Sleep and Indoor Air Quality - Lan, Li; Lian, Zhiwei (Handbook of Indoor Air Quality, 2021)
Keywords: _important

A survey of bedroom ventilation types and the subjective sleep quality associated with them in Danish housing - Liao, Chenxi; Akimoto, Mizuho; Bivolarova, Mariya Petrova; Sekhar, Chandra; Laverge, Jelle; Fan, Xiaojun; Lan, Li; Wargocki, Pawel (Science of The Total Environment, 2021)
We performed a survey of the types of bedroom ventilation in Danish dwellings (January–February 2020) and the associated subjective sleep quality. Five hundred and seventeen people responded. Their median age was 33 years old and 55.4% of them were males. We used an online questionnaire and collected information on the type of bedroom ventilation, bedroom airing behaviour by the respondents, the bedroom environment, building surroundings and location, and sleep disturbance caused by stuffy air, noise, and the thermal environment. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI); its median among respondents was >5 indicating reduced sleep quality. 35.4% of the bedrooms had mechanical, 24.6% exhaust, and 40.0% natural ventilation. Sleeping in a bedroom with mechanical ventilation tended to reduce sleep disturbance. The absence of mechanical ventilation and the presence of carpet in the bedroom were all associated with stuffy air causing sleep disturbance, which was the second most sleep disturbing factor. PSQI increased significantly with increased sleep disturbance. People who reported that their sleep was disturbed by stuffy air or “too warm” conditions opened windows frequently during the day or night, but no association was found between PSQI and bedroom airing behaviours. Our results are valid for the heating season and the survey would have to be repeated in the non-heating season to permit generalization of the findings. The results present associations and are qualitative, so field measurements are necessary to validate the present observations and provide further explanations.
Keywords: BE:RELEVANT; Noise; Occupant behaviour; PSQI; Sleep disturbance; Stuffy air; Thermal comfort; _z:class:countries; _z:class:themes; oa:keyword:bedroom ventilation types; oa:keyword:subjective sleep quality; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10316 Sleep and Insomnia; oa:topic:T11692 Effects of Noise Pollution on Health and Well-being; openalex:n:1; openalex:yes